The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/pce.12494
|View full text |Cite
|
Sign up to set email alerts
|

How membranes organize during seed germination: three patterns of dynamic lipid remodelling define chilling resistance and affect plastid biogenesis

Abstract: Imbibitional chilling injury during germination causes agricultural losses but this can be overcome by osmopriming. It remains unknown how membranes reorganize during germination. Herein, we comparatively profiled changes of membrane lipids during imbibition under normal and chilling temperatures in chilling-tolerant and -sensitive soybean seeds. We found three patterns of dynamic lipid remodelling during the three phases of germination. Pattern 1 involved a gradual increase in plastidic lipids during phases I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 54 publications
2
55
0
1
Order By: Relevance
“…Although nuclear-encoded, the shikimate pathway and other biosynthetic processes take place at the plastids, which are largely non-functional in dry seeds. However, a recent study demonstrated that plastid biogenesis starts early in phase I of soybean germination58. Therefore, we hypothesize that newly generated plastids get promptly equipped with the shikimate and other biosynthetic pathways.…”
Section: Resultsmentioning
confidence: 87%
“…Although nuclear-encoded, the shikimate pathway and other biosynthetic processes take place at the plastids, which are largely non-functional in dry seeds. However, a recent study demonstrated that plastid biogenesis starts early in phase I of soybean germination58. Therefore, we hypothesize that newly generated plastids get promptly equipped with the shikimate and other biosynthetic pathways.…”
Section: Resultsmentioning
confidence: 87%
“…et al (2006) indicaron que, durante la imbibición, el incremento del peso de las semillas de Swietenia macrophylla fue sólo significativo en las dos primeras fases; es decir, la de absorción rápida para luego no absorber agua por un cierto tiempo (hasta la protrusión de la radícula). En conductividad eléctrica las semillas de Roque B16 en remojo por 6 y 12 h superaron al testigo (5.54 µs cm -1 ), la conductividad eléctrica se basa en el principio de que conforme las semillas se deterioran, altera la permeabilidad diferencial de las membranas celulares, de manera que, al ser colocadas en una solución acuosa, la semilla menos vigorosa sufre perdida de compuestos citoplasmáticos como aminoácidos, iones y azúcares de bajo peso molecular, al ser rehidratadas las semillas deben tener la capacidad de reorganizar las membranas para evitar la pérdida de solutos (Yu et al, 2015).…”
Section: Resultados Y Discusiónunclassified
“…Because of chilling injury at unfavorable, low temperature, the cell membrane of cold-sensitive plants undergoes phase changes, and this affects its function and structural integrity [15]. Studies on loquats and peaches showed that the higher the unsaturated fatty acid level in the cell membrane, the higher the fluidity and stability of the cell membrane; this stability is beneficial and increases resistance of fruits to chilling injury.…”
Section: Discussionmentioning
confidence: 99%